2004
DOI: 10.1063/1.1829974
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution pulsed-field-ionization zero-kinetic-energy photoelectron spectroscopic study of the two lowest electronic states of the ozone cation O3+

Abstract: The pulsed-field-ionization zero-kinetic-energy ͑PFI-ZEKE͒ photoelectron spectrum of jet-cooled O 3 has been recorded in the range 101 000-104 000 cm Ϫ1 . The origins of the X 1 A 1 →X ϩ 2 A 1 and X 1 A 1 →Ã ϩ 2 B 2 transitions could be determined from the rotational structure of the bands, the photoionization selection rules, the photoionization efficiency curve, and comparison with ab initio calculations. The first adiabatic ionization energy of O 3 was measured to be 101 020.5(5) cm Ϫ1 ͓12.524 95͑6͒ eV͔ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…However, the resolution achieved in these investigations was not sufficient in order to determine whether the ground state is the 2 A 1 or the 2 B 2 component. The experimental confirmation of the theoretical prediction that theX + state is of 2 A 1 electronic symmetry [101][102][103] has only been achieved recently by the analysis of the rotational structure of the high-resolution PFI-ZEKE photoelectron spectrum which also showed that the origins of theX + andà + states are only separated by 1089.7 cm −1 [41]. This confirmation was performed on the basis of symmetry assignments and of simulations of the bands using the orbital ionization model.…”
Section: Assigning the Vibronic Symmetry Of Photoelectron Bands With mentioning
confidence: 92%
See 2 more Smart Citations
“…However, the resolution achieved in these investigations was not sufficient in order to determine whether the ground state is the 2 A 1 or the 2 B 2 component. The experimental confirmation of the theoretical prediction that theX + state is of 2 A 1 electronic symmetry [101][102][103] has only been achieved recently by the analysis of the rotational structure of the high-resolution PFI-ZEKE photoelectron spectrum which also showed that the origins of theX + andà + states are only separated by 1089.7 cm −1 [41]. This confirmation was performed on the basis of symmetry assignments and of simulations of the bands using the orbital ionization model.…”
Section: Assigning the Vibronic Symmetry Of Photoelectron Bands With mentioning
confidence: 92%
“…Fig. 2 shows a schematic representation of the relevant molecular orbitals of O 3 together with the most important configurations contributing to theX 1 A 1 ,X + 2 A 1 andà + 2 B 2 states as predicted by theory [98,41]. Because of configuration interaction, theX + state of O + 3 is not formed by ionization out of the HOMO, the 1a 2 orbital.…”
Section: Assigning the Vibronic Symmetry Of Photoelectron Bands With mentioning
confidence: 98%
See 1 more Smart Citation
“…The validity of the suggestion is seen from figure 2. It seems , is 0.6 eV [24]. It is likely that the likelihood of the bond rupture increases with the weakness of the bond.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of biradical character varies inversely with the singlet-triplet energy splitting, which in ozone is rather large. Note that recent ab initio configuration interaction calculations [12] have shown that the electronic structure of ozone is dominated by a single determinant, arguing against a significant biradical character and explaining why DFT captures the structure and energetics of ozone well.…”
Section: Introductionmentioning
confidence: 97%